COMPARATIVE STUDIES ON SEDATIVE AND ANALGESIC EFFECTS OF XYLAZINE AND DETOMIDINE IN GOATS - Shah; Z.; A. B. Kalhore; A. B. Kachiwal; I. Ahmad; H; Sattar; M. A. Khan; Z. U. Rehman; F. A. Khan; T. Hussain; H. A. Ullah (Journal of Animal and Plant Sciences, 2013)
An experiment was carried out to compare the sedative and analgesic effects of intravenous administration of xylazine (0.1mg/kg) and detomidine (50μg/kg), in six healthy goats (Bari breed). Onset of sedation occurred within 29 ± 3.74 and 55.66 ± 5.57 seconds which lasted for 77.59 ± 4.38, and 85.38 ± 2.76 minutes with xylazine and detomidine, respectively. Skin analgesia occurred within 5.66 ± 3.26, and 12. 83 ± 3.48 minutes and the mean values for duration of analgesia were 40.66 ± 3.32 and 33.5 ± 3.67 minutes after administrations of xylazine and detomidine, respectively. Moderate to deep degree of analgesia was achieved by the administration of xylazine and detomidine. Some side effects like salivation, frequent urination, defecation, tympany, protrusion of the tongue, head drooping and bellowing were observed after administration of xylazine and detomidine. It is concluded that these alpha-2 adrenergic agonists are safe to be used in goats.
Keywords: Sedation; goat; analgesia; detomidine; xylazine